High feasibility of salivary therapeutic drug monitoring in linezolid, but lower feasibility in tedizolid: a single-dose study in healthy subjects and a monocentric prospective exploratory study in patients who received linezolid - Kawasuji, Hitoshi; Tsuji, Yasuhiro; Miyaki, Keiko; Aoyama, Takahiko; Kurosaki, Fumihiro; Ezaki, Masayoshi; Koshiyama, Yuki; Takegoshi, Yusuke; Kaneda, Makito; Murai, Yushi; Kimoto, Kou; Nagaoka, Kentaro; et al. (Journal of antimicrobial chemotherapy, 2025)
Salivary therapeutic drug monitoring (TDM) offers the potential to reduce the risks, burden, time and costs of blood-based TDM, but its feasibility for use with oxazolidinone antibiotics and the influence of food intake remain unknown. We conducted a healthy subject study with 12 healthy participants. Linezolid and tedizolid were intravenously administered to 6 participants each. Saliva and peripheral venous blood samples were taken simultaneously at 12 time points and their correlations were evaluated, including a determination of whether these correlations were sustained after food intake. A monocentric prospective exploratory study was then conducted in 10 patients. Total and unbound serum and saliva concentrations were measured using high-performance liquid chromatography. In healthy participants administered linezolid, individual concentration-time curves for saliva were similar to those for serum (total and unbound), but the saliva and serum concentration-time curves differed for tedizolid. Saliva concentrations in each case and area under the concentration-time curve from 0 to 10 h (AUC0-10) in saliva were correlated with those in total or unbound serum for linezolid, but not for tedizolid. Food intake did not influence the correlations in linezolid. In the exploratory study in 10 patients administered linezolid, saliva concentrations correlated with total or unbound serum concentrations in both non-haemodialysis (n = 7) and haemodialysis (n = 3) patients, irrespective of dosages, administration routes, timing or eating and drinking restrictions. Salivary TDM is a promising alternative to conventional serum sampling for linezolid but is less feasible for tedizolid.